Impact of Complex Quality-Interventions on Patient Outcome: A Systematic Overview of Systematic Reviews. (November 2019) - Walther, Felix; Kuester, Denise; Schmitt, Jochen
Quality of care and the increasing strategies to its promotion, especially in inpatient settings, led to the question which quality-interventions work best and which do not. The aim was to summarize and critically appraise the evidence on the effects of structure- and/or process-related quality-interventions on patient outcome in predominantly controlled and inpatient settings. A systematic overview of systematic reviews after electronic searches in Medline, Embase, Cinahl, and PsycINFO, supplemented by hand search and expert survey, was conducted. From a total of 1559 identified records, 37 reviews fulfilled the inclusion criteria. 26 reviews assessed process-related quality-interventions, 6 structure-related quality-interventions, and 5 combined structure- and process-related quality-interventions. In all, 19 reviews reported pooled effect estimates (meta-analysis). Based on the evidence of this systematic overview, stroke units and pathways can be recommended. Although patient-relevant improvements for interprofessional approaches and discharge planning have been reported, pooled effect estimated evidence are currently missing for these and other quality-interventions.